MEMBIMBING PENERAPAN PENILAIAN AUTENTIK MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA GURU SDN 1 PERUMNAS WAY HALIM BANDAR LAMPUNG - Putri Mauli (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
The purpose of this PTS is to increase competency in applying authentic assessment techniques through the Contextual Teaching And Learning (CTL) Approach to Teachers in SD Negeri 1 Perumnas Way Halim Bandar Lampung in 2018. Data collection techniques in this study were obtained through observation and field data notes, interviews, and notes on the results of reflections / discussions on the application of authentic assessment techniques conducted by the teacher, in this case the researchers partner with partners and colleagues. Guidance activities on the application of the CTL approach to teachers in SD Negeri 1 Perumnas Way Halim have been well implemented and are contributing to the improvement of teachers' understanding and pedagogical competence in authentic assessment techniques. The results of Cycle I Coaching reached 36 (60%), Comprehension 32 (53%), Application of 35 (58%), Cycle II Coaching reached 49 (81%), Comprehension 52 (86%), Leading 46 (77%), Cycle III Guidance reached 55 (92%), Understanding 57 (95%), Leading 53 (88%). The conclusion of this study states that the Contextual Teaching And Learning (CTL) approach can improve the Pedagogical Competence of Authentic Assessment Techniques in Way Halim 1 Elementary School Teachers in Bandar Lampung, 2018.